From lignin to cycloparaffins and aromatics: Directional synthesis of jet and diesel fuel range biofuels using biomass. (May 2015) - Bi, Peiyan; Wang, Jicong; Zhang, Yajing; Jiang, Peiwen; Wu, Xiaoping; Liu, Junxu; Xue, He; Wang, Tiejun; Li, Quanxin
Graphical abstract: A novel controllable transformation of lignin into C8–C15 cycloparaffins and aromatics in the jet and diesel fuel range by catalytic depolymerization of lignin into low carbon aromatics coupled with alkylation of aromatics using ionic liquid. Highlights: A controllable transformation of lignin into green bio-jet fuels was demonstrated. Production of C8–C15 hydrocarbons was achieved by alkylation using ionic liquid. Lignin-derived biofuels basically met main technical requirements of jet fuels. Abstract: The continual growth in commercial aviation fuels and more strict environmental legislations have led to immense interest in developing green aviation fuels from biomass. This paper demonstrated a controllable transformation of lignin into jet and diesel fuel range hydrocarbons, involving directional production of C8–C15 aromatics by the catalytic depolymerization of lignin into C6–C8 low carbon aromatic monomers coupled with the alkylation of aromatics, and the directional production of C8–C15 cycloparaffins by the hydrogenation of aromatics. The key step, the production of the desired C8–C15 aromatics with the selectivity up to 94.3%, was achieved by the low temperature alkylation reactions of the lignin-derived monomers using ionic liquid. The synthetic biofuels basically met the main technical requirements of conventional jet fuels. The transformation potentially provides a useful way for the development of cycloparaffinic and aromatic components in jet fuels using renewable lignocellulose biomass.